'It might hurt, but still it's good': People with rheumatoid arthritis beliefs and expectations about physical activity interventions. (November 2017) - Larkin, Louise; Kennedy, Norelee; Fraser, Alexander; Gallagher, Stephen
Many people who have rheumatoid arthritis report low levels of physical activity. We conducted 17 interviews with people who have rheumatoid arthritis to gain insight into how they view physical activity and to explore how their levels of activity may be increased. Interviews were transcribed verbatim and analysed using thematic analysis. Four main themes were generated: being active, barriers and facilitators, information and advice, and supporting physical activity. A lack of information about being active fostered negative emotions limiting physical activity participation. Improved provision of physical activity advice is warranted to promote physical activity in people who have rheumatoid arthritis.